Profile of Junior High School Students' Constraints in Online Science Learning - Desy Suryani; Eko Hariyono; Tjipto Prastowo (IJORER : International Journal of Recent Educational Research, 2021)
This research aims to determine the online learning constraints of Junior High School students in Nganjuk on science subjects. The change in learning methods that were originally carried out face-to-face to online learning experienced several obstacles such as internet connection, lack of enthusiasm for learning, difficult materials, unclear teaching materials, and teacher’s teaching methods. The type of this research is descriptive survey research, the data of this research was obtained from 70 junior high school students in Nganjuk. The data collection technique in this research was a questionnaire (questionnaire) while the instrument used in this research was an online Google Form questionnaire, which is distributed through the WhatsApp application. The data analysis technique used in this research is descriptive analysis. The results showed that the most common obstacle felt by junior high school students in Nganjuk was the lack attractiveness of teaching materials.